Effectiveness of Prophylactic Antiemetic Regimen to Anthracycline Chemotherapy - S, Sivasankar; Prasath, Mahendra; Y, Yookanithya; Kumar, Dinesh; Rangarajan, Bharath (Indian Journal of Pharmacy Practice)
Objectives: The availability of efficacy and safety profile of prophylactic antiemetic medications in various high emetogenic chemotherapy protocols will make it a valuable therapeutic option for healthcare provider. Hence this research aimed to assess the comparative safety and efficacy of prophylactic antiemetic regimen during anthracycline chemotherapy and their impact on Quality of Life (QoL). Materials and Methods: This is a prospective, observational study that included 55 patients with anthracycline Chemotherapy. The Common Terminology Criteria for Adverse Events (CTCAE) version 5.0 was used to grade cases of nausea and vomiting. We assessed the percentage of complete response and complete control of CINV and health- related quality of life was assessed using the Functional Living Index-Emesis (FLIE), a 5-day recall tool. Statistical analysis: The Statistical Package for the Social Sciences (SPSS) Statistics for Windows, Version 16.0 (IBM Corp, Armonk, NY) was used to conduct the statistical analysis. A P-value of less than 0.05 was deemed to indicate statistical significance. Results: The complete response rates for NEPD/ APD and NEOPD/AOPD were 91.66% and 89.47%, respectively, whereas the complete control rates were 55.55% and 52.63%. In the CTCAE version 5.0 studies, only 3.6% of nausea and 1.8% of vomiting cases were classified as Grade 3, with no cases classified as Grade 4 or 5. The FLIE score was greater than 54 in the vomiting domain and less than 54 in the nausea domain, indicating that CINV had a minimal impact on daily life. Conclusion: This observational study showed that both NEPD/APD and NEOPD/AOPD regimens had similar efficacy and safety profiles in managing nausea and vomiting during anthracycline-based chemotherapy, with minimal impact on QoL and mild adverse events.
Keywords: Anthracyclines; Antiemetics; Prophylactics; Quality of Life; Chemotherapy